Systematic Evaluation for the Influences of the SOX17/Notch Receptor Family Members on Reversing Enzalutamide Resistance in Castration-Resistant Prostate Cancer Cells - Du, Zhongbo; Li, Luo; Sun, Wei; Zhu, Pingyu; Cheng, Shulin; Yang, Xuesong; Luo, Chunli; Yu, Xiaodong; Wu, Xiaohou (Frontiers in Oncology, 2021)
The treatment of castration-resistant prostate cancer (CRPC) remains challenging due to the failure of androgen deprivation therapy（ADT）, hence the search for other molecular therapeutic targets besides androgen receptor signaling is ongoing. This study systematically investigated the expression of SOX17 and Notch receptors in CRPC tissues and cells in vitro, showing that consistent clinical CRPC, SOX17/Notch1 and Notch4 were responsible for enzalutamide resistance in CRPC cells. The γ secretase inhibitors, BMS-708163, GSI-IX, PF-3084014, and RO4929097 abrogated the enzalutamide resistance by inhibiting Notch1 or/and Notch4 in vitro, with GSI-IX and RO4929097 being more effective than BMS-708163 and PF-3084014 in reliving bone metastasis in vivo. In conclusion, the Notch1 and Notch4 inhibitors GSI-IX and RO4929097 are promising therapeutic agents for the treatment of CRPC.